A Statistical Damage Constitutive Model for Geomaterials under Plane-Strain Biaxial Stress State. (17th October 2017) - Zhang, Hongwei; Wan, Zhijun; Wang, Chaoyi; Ma, Zhaoyang; Zhang, Yuan; Cheng, Jingyi
Abstract : The mechanical behavior of geomaterials under plane-strain biaxial stress state (PSBSS, a special case of biaxial stress state) is often considered in geotechnical structures such as highwall and longwall coal pillars. In this study, a modified statistical damage constitutive model based on Weibull distribution was established to explain the mechanical behavior of rocks under the PSBSS. The modified Wiebols-Cook criterion, Drucker-Prager criterion, and extremum method were adopted in this model to estimate the peak strength of rock, the strength level of microscopic element, and the statistical parameters of model, respectively. Besides, laboratory tests for brittle and ductile geomaterials under PSBSS were conducted using the modified surface instability detection apparatus to validate the accuracy of the proposed statistical damage model. Finally, the relationships between mechanical parameters and statistical parameters were studied and discussed.